Organizational Citizenship Behavior and Gray Matter Volume Among Japanese Workers: An Exploratory Cross‐Sectional Study - Keisuke Kokubun; Kiyotaka Nemoto; Yoshinori Yamakawa (Brain Health, 2026)
ABSTRACT Introduction Organizational citizenship behavior (OCB) is generally considered beneficial to organizations, but extra‐role behavior may also impose costs on employees under some circumstances. Whether the workplace, personality, and neuroanatomical correlates of OCB differ between men and women remains unclear. Methods We examined 71 Japanese workers (34 men and 37 women) using measures of OCB, person–environment (P‐E) fit, Big Five personality traits, burnout, and gray matter Brain Healthcare Quotient (GM‐BHQ). Prespecified P‐E fit hypotheses were examined using parsimonious sex‐stratified models. Sex differences in personality, GM‐BHQ, and burnout associations were evaluated using formal interaction tests. Primary neuroimaging models included OCB, sex, sex × OCB interaction, age, and intracranial volume (ICV). Multiplicity was controlled within defined hypothesis families using the Holm procedure, and 95% confidence intervals were reported. Results Among men, higher OCB was associated with lower control fit and higher community fit after multiplicity correction. Among women, higher OCB was associated with higher reward fit, whereas the hypothesized negative association with workload fit was not statistically significant. Formal interaction analyses provided no evidence that personality correlates of OCB is differed by sex. None of the sex × OCB interactions across the 12 GM‐BHQ measures was statistically significant; for subcortical GM‐BHQ, the interaction was β = −0.117 (95% CI [−0.519, 0.285], p = 0.563). Secondary sex‐stratified analyses suggested a negative association between OCB and subcortical GM‐BHQ among women, but this finding was sensitive to covariate specification and did not survive multiplicity correction. No evidence of sex modification was observed for burnout. Conclusion The present study did not provide evidence that sex modifies the association between OCB and brain structure. Although some prespecified P‐E fit associations were observed within sex, the neuroimaging findings were exploratory and did not establish sex‐specific neuroanatomical associations. Larger, prospectively designed studies with adequately powered interaction tests are required.